The Role of Health Policy in Achieving Justice for Indonesia’s Disadvantaged Communities (Indonesian Health Justice Review, 2024)
Health policy plays a critical role in promoting health justice by addressing the needs of disadvantaged communities, including low-income, rural, and indigenous populations. This paper explores how health policies in Indonesia can better serve marginalized groups and reduce health inequities. Through a policy analysis of Indonesia’s healthcare system, including Universal Health Coverage (UHC) and specific health interventions for vulnerable populations, the research identifies both strengths and weaknesses in current policy frameworks. Key findings indicate that while UHC has expanded healthcare access, it does not fully address the social determinants of health, such as poverty, education, and housing, which disproportionately affect disadvantaged communities. Additionally, healthcare facilities in rural and remote areas remain underfunded and understaffed. The paper argues that achieving health justice in Indonesia requires a holistic approach that combines equitable healthcare access with policies that tackle the root causes of health disparities. Recommendations include increasing investments in health infrastructure, integrating social protection policies, and strengthening community-based healthcare models.